Elastomeric Recombinant Protein-based Biomaterials - Annabi, Nasim (2013)
Elastomeric protein-based biomaterials, produced from elastin derivatives, are widely investigated as promising tissue engineering scaffolds due to their remarkable properties including substantial extensibility, long-term stability, self-assembly, high resilience upon stretching, low energy loss, and excellent biological activity. These elastomers are processed from different sources of soluble elastin such as animal-derived soluble elastin, recombinant human tropoelastin, and elastin-like polypeptides into various forms including three dimensional (3D) porous hydrogels, elastomeric films, and fibrous electrospun scaffolds. Elastin-based biomaterials have shown great potential for the engineering of elastic tissues such as skin, lung and vasculature. In this review, the synthesis and properties of various elastin-based elastomers with their applications in tissue engineering are described.